Beyond the human touch: Can generative AI transform Uganda’s agricultural extension and advisory services? - Asiimwe, Elizabeth; Davis, Kristin E. (Uganda Forum for Agricultural Advisory Services, 2025)
Generative Artificial Intelligence (Gen AI) is a type of artificial intelligence that can create new content such as text, images, audio, video, or even computer code, based on the data it has been trained on. Generative AI is trained on huge amounts of data (like books, images, and conversations), and it learns patterns. When prompted, it uses the learned patterns to generate something new that fits the request.